Solving Robin problems in bounded doubly connected regions via an integral equation with the eneralized Neumann Kernel - Hussein, Shwan Hassan (2015)
This paper presents a boundary integral equation method for finding the solution of Robin problems in bounded multiply connected regions. The Robin problems are formulated as a Riemann-Hilbert problems which lead to systems of integral equations and the related differential equations are also constructed that give rise to unique solutions are shown. Numerical results on several test regions are presented to illustrate that the approximate solution when using this method for the Robin problems when the boundaries are sufficiently smooth are accurate.